Viral Marketing, Brand Ambassador, Online Consumer Review, Consumer Trust, and Purchase Decision - Ni Wayan Ika Widyastuti; Gede Sri Darma (Yayasan Riset dan Pengembangan Intelektual, 2024)
The personal care and beauty industry is an industry in the chemical, pharmaceutical and traditional medicine industry sector that continues to grow consistently in Indonesia as a country that has the potential to become one of the top 5 largest economies in the world. This makes the competitive conditions in the skincare industry competitive, forcing business actors to make efforts to encourage consumers to make purchases on their brands. This study aims to test the effect of viral marketing, brand ambassadors, online consumer reviews and consumer trust on purchase decisions in skincare users. This study was conducted quantitatively on 180 respondents domiciled in Bali, Indonesia. The results of this study indicate that viral marketing and online consumer reviews do not have a significant influence on purchase decisions, while brand ambassadors and consumer trust do not have a significant influence on purchase decisions. This shows how important digitalization is as a consideration for consumers today.